Kadar Protein, Daya Kembang, dan Organoleptik Cookies dengan Substitusi Tepung Mocaf dan Tepung Pisang Kepok - Anik Sholekah Oktaviana; Wikanastri Hersoelistyorini; Nurhidajah Nurhidajah (Jurnal Pangan dan Gizi, 2017)
ABSTRACT Cookies are small snacks that are very popular in many people. Cookies use a wheat flour with low-protein that can be substituted with mocaf and flour of banana’s kepok. The general objective of this study was to determine the protein content, swell power and the organoleptic characteristic of cookies based mocaf and flour of banana’s kepok. The experimental method of experimental type using Completely Randomized Design (CRD) monofactor with variation factor of 0: 0, 1: 9, 3: 7, 1: 1, 7: 3, and 9: 1 (mocaf flour: flour of banana’s kepok). Cookies analyzed levels of protein, swell power and organoleptic characteristic. Protein content and swell power data were analyzed by ANOVA statistic followed by Duncan test while organoleptic characteristic test was analyzed using Friedmann test and Wilcoxon test. The results of statistical analysis showed that there was an effect of the amount of substitution of mocaf flour and flour of banana’s kepok on protein content, swell power and organoleptic organoleptic in terms of color. The best results of this study were substitution cookies of mocaf 5% and flour of banana’s kepok 45% with 4.19% protein content, 23.89% swell power and average value of organoleptic characteristic 3.01 substitution from  cookies of mocaf 45% and flour of banana’s kepok 5%. Conclusions of the research conducted on substitution cookies of mocaf and flour of banana’s kepok showed no real difference for each test performed, except the organoleptic characteristic in terms of taste, aroma and texture. Keyword: mocaf, banana’s kepok, cookies, swell power, and organoleptic characteristic